Thermal performance of acrylonitrile butadiene styrene dipped in graphene oxide suspensions - Mohammadsalih, Zaid G.; Sadeq, Noor S.; Salit @ Sinon, Mohd Sapuan (Taylor and Francis, 2024)
The preparation of polymer nanocomposites (PNCs) by employing green, efficient, and cost effective approach rather than the traditional ways of preparation is considered as a key challenge. In this work, an eco-friendly and cost-effective approach represented by dipping of Acrylonitrile Butadiene Styrene (ABS) pellets in Graphene Oxide (GO) suspensions of different concentrations was adopted to prepare the nanocomposites and improve their thermal performance. GO powder was prepared by Improved Hummers’ method, and four different concentrations of GO (0.1, 0.2, 0.3 and 1.0) mg/ml suspended stably via ultrasonication in distilled water. 2.0 g of ABS was dipped in each GO concentration for 20 minutes and then, hot-pressed in order to obtain disc-like samples. The findings showed a successful preparation and adherence of GO to ABS that was confirmed by optical microscopy (OM) and Raman spectroscopy. An improvement in thermal properties of glass transition temperature (Tg) and endothermic temperature was achieved for the ABS pellets dipped in GO suspensions compared to the undipped neat polymer. © 2024 Taylor & Francis Group, LLC.